Plasma neurofilament light chain levels suggest neuroaxonal stability following therapeutic remyelination in people with multiple sclerosis. Issue 9 (16th June 2022) - Abdelhak, Ahmed; Cordano, Christian; Boscardin, W John; Caverzasi, Eduardo; Kuhle, Jens; Chan, Brandon; Gelfand, Jeffrey M; Yiu, Hao H; Oertel, Frederike C; Beaudry-Richard, Alexandra; Condor Montes, Shivany; Oksenberg, Jorge R; et al.
Abstract : Background: Chronic demyelination is a major contributor to axonal vulnerability in multiple sclerosis (MS). Therefore, remyelination could provide a potent neuroprotective strategy. The ReBUILD trial was the first study showing evidence for successful remyelination following treatment with clemastine in people with MS (pwMS) with no evidence of disease activity or progression (NEDAP). Whether remyelination was associated with neuroprotection remains unexplored. Methods: Plasma neurofilament light chain (NfL) levels were measured from ReBUILD trial's participants. Mixed linear effect models were fit for individual patients, epoch and longitudinal measurements to compare NfL concentrations between samples collected during the active and placebo treatment period. Results: NfL concentrations were 9.6% lower in samples collected during the active treatment with clemastine (n=53, geometric mean=6.33 pg/mL) compared to samples collected during treatment with placebo (n=73, 7.00 pg/mL) (B=−0.035 [−0.068 to −0.001], p=0.041). Applying age- and body mass index-standardised NfL Z-scores and percentiles revealed similar results (0.04 vs 0.35, and 27.5 vs 33.3, p=0.023 and 0.042, respectively). Higher NfL concentrations were associated with more delayed P100 latencies (B=1.33 [0.26 to 2.41], p=0.015). In addition, improvement of P100 latencies between visits was associated with a trend for lower NfL values (B=0.003 [−0.0004 to 0.007], p=0.081). Based on a Cohen's d of 0.248, a future 1:1 parallel-arm placebo-controlled study using a remyelinating agent with comparable effect as clemastine would need 202 subjects per group to achieve 80% power. Conclusions: In pwMS, treatment with the remyelinating agent clemastine was associated with a reduction of blood NfL, suggesting that neuroprotection is achievable and measurable with therapeutic remyelination. Trial registration number: NCT02040298 .